Is There Any Relationship Between Varicocele and Reproductive Hormone Status in Non-obstructive Azoospermia? - Özman, Oktay; Çitgez, Sinharib; Bülbül, Emre; Şahin, Kadir Can; Özkara, Hamdi (Cerrahpaşa Medical Journal, 2021)
Objective: The aim of this study was to compare the reproductive hormone parameters according to the presence or absence of varicocele in patients having non-obstructive azoospermia. Methods: A total of 111 non-obstructive azoospermic men were included in the study retrospectively. The patients were divided into 2 groups according to the presence of varicocele. Thirty of 111 patients had varicocele (group 1). Control group was formed with 81 patients (group 2). Two groups were compared in terms of serum total testosterone, follicle-stimulating hormone, and luteinizing hormone. Results: Physical examination revealed varicocele in 10.8% (95% CI: 0.0854-0.1348) of the main cohort of non-obstructive azoospermia patients. Mean total testosterone level was higher in patients with varicocele compared to the other group (585 ± 412 ng/dL and 423 ± 167 ng/dL, respectively) (P = .002). The mean follicle-stimulating hormone level was lower in patients with varicocele (group 1) than patients without varicocele (group 1: 17.72 ± 13.2 mIU/mL, group 2: 21.69 ± 16.6 mIU/mL). However, this difference was not statistically significant (P = .38). Conclusions: Serum testosterone levels of non-obstructive azoospermic men with varicocele are higher than men with idiopathic nonobstructive azoospermia. Looking from azoospermia as an endpoint of the spermatogenic failure, varicocele appears to affect testicular hormone production less than idiopathic etiology which can be attributed to genetic causes. Cite this article as: Özman O, Çitgez S, Bülbül E, Şahin KC, Özkara H. Is there any relationship between varicocele and reproductive hormone status in non-obstructive azoospermia? Cerrahpaşa Med J. November 20, 2021. 46(1):17-20.